TBEV analyzer platform for evolutionary analysis and monitoring tick-borne encephalitis virus: 2020 update. Issue 1 (2nd January 2022) - Forghani, Majid; Kovalev, Sergey; Bolkov, Mikhail; Khachay, Michael; Vasev, Pavel
Abstract : Viral surveillance is an essential task in public health that yields specific data, such as biological and epidemiological characteristics, crucial in the fight against viruses. We have recently developed an online platform for monitoring of Tick-Borne Encephalitis Virus, TBEV Analyzer, equipped with phylogenetic analysis and geographic map visualization functions. The phylogenetic analysis employs the clusteron approach, which has been earlier proposed by one of the authors of this paper. The analysis is based on a genetic pattern and provides three-fold hierarchical information about subtype, phylogenetic lineage, and clusteron. A clusteron is a group of TBEV strains with identical amino acid sequences of the glycoprotein E fragment, as a rule phylogeographically close, and having a certain type of territorial distribution. We enhance the algorithms and quality of visualization by integrating our platform with the GenBank database, adding a heat map distribution, and providing more details in the analysis report. To demonstrate the performance of the upgraded system, we analyze recent strains published in GenBank and compare them with the results of the manual analysis performed by a specialist. The results show that the system can rapidly and accurately determine query strain characteristics. This suggests possible applications in the field of public health.